Efektivitas Jenis Pelarut dan Metode Ekstraksi dari Daun Talas (Colocasia esculenta L. Schoot) - Sulistiani, Ria Purnawian; Isworo, Joko Teguh (Jurnal Gizi, 2022)
Taro leaves (Colocasia esculenta L. Schoot) are widely used as vegetables and herbal medicines. In proving taro leaves as herbal medicine, taro leaves are changed in the form ofextract preparations. The choice of extraction method will affect the results of flavonoid levelsand antioxidant activity. Extraction methods that are widely used to extract taro leaves aremaceration and soxhletation. Maceration extraction method, the sample was immersed in 1000ml of ethanol and 1000 ml of n-hexane for 3 x 24 hours. Every 24 hours replaced with a newsolvent. Extracts were made by soxhletation method using ethanol as solvent and the other usingn-hexane as solvent. The material that has been submerged in petroleum ether is wrapped infilter paper and then tied with thread. Then it is put into the socket extractor. Furthermore, theflavonoid and antioxidant levels were tested. The highest flavonoid content in taro leaves wasobtained by maceration method with ethanol solvent, as much as 12.836 mg QE/g. The highestantioxidant activity was 91.812% by maceration method and n-hexane solvent. The macerationmethod with n-hexane solvent can obtain taro leaf extract which has high antioxidant activity. Kata Kunci—Antioksidan, Colocasia esculenta, Ekstraksi, Flavonoid, Pelarut